SENTIMENT ANALYSIS OF PERFORMANCE EFFECTIVENESS OF MALIOBORO PEDESTRIAN USING SENTISTRENGTH METHOD ON TWITTER - Uning Lestari; Debby Anugrahni (Jurnal TAM (Technology Acceptance Model), 2021)
Sentiment analysis is a study to analyze public opinions, sentiments, evaluations, attitudes, and emotions towards services, products, public issues, organizations, general topics, etc. Sentiment analysis is a computational research of various opinions and emotionsexpressed textually and opinions in the form of text can be obtained through social media such as Twitter. The Malioboro area as one of the famous tourist destinations in Yogyakarta has pedestrian facilities for visitors. In the area, there are many pedestrian facilities including pedestrian paths, sidewalks, zebra crossings and parking. This study aims to measure the effectiveness of the use of the pedestrian area in Malioboro based on opinions on Twitter. This study uses the Sentistrength method. The results shows that from 3,572 Tweet data from 2016 to 2020, the results of Positive sentiment are 55.81%, the results of Neutral sentiment are 36.18% and the results of negative sentiment are 8.01%.